A single-institution experience with laparoendoscopic single-site retroperitoneal adrenalectomy - Yu-Chen Chen; Hsiang-Ying Lee; Hao-Wei Chen; Hsin-Chih Yeh; Chia-Chun Tsai; Kuang-Shun Chueh; Yii-Her Chou; Chun-Nung Huang; Wen-Jeng Wu; Nien-Ting Hou; Yech-Huei Lin; Ching-Chia Li (Urological Science, 2018)
Aims: Laparoendoscopic single-site (LESS) adrenalectomy has become a feasible choice for adrenal lesions and can substitute for conventional open adrenalectomy. This report shares our surgical experience and describes the characteristics of adrenal tumors after LESS retroperitoneal adrenalectomy. Subjects and Methods: Between January 2010 and August 2016, 123 patients underwent an LESS adrenalectomy by retroperitoneal approach in our hospital. We retrospectively reviewed the records of these patients and analyzed the characteristics of adrenal tumors. The incision is below the 12th rib in the posterior axillary line and is about 2.3–3.2 cm in length. A 5 mm 30° rigid laparoscope and other conventional laparoscopic instruments are manipulated through a commercial port. No postoperative drain is placed. Results: Among 123 patients, the mean operative time was 114.1 ± 31.1 min, and mean blood loss was 65.1 ± 68.7 ml. Mean hospital stay was 5.4 ± 1.2 days. The postoperative course was uneventful without complications. Among all adrenal tumors undergoing surgery, Conn's disease is the most common (68.3% Conn's disease, 19.5% nonfunctioning, 4.9% Cushing's disease, 3.3% pheochromocytoma, and 0.8% malignancy). We found that left-side adrenal tumors (64.2%) were more common than right-side tumors (35.8%). Conclusions: Our experience shows that retroperitoneal LESS adrenalectomy is promising. Conn's disease accounts for more than half of adrenal tumors undergoing surgery. In the future, further comparative study is warranted to define the role of LESS in adrenal surgery.